(untitled) (Journal of Information Technologies in Education (ITE), 2023)
The article scientifically researches the theoretical, methodological, and analytical aspects of the quality of education in distance learning using ICT. Attention was drawn to such aspects as the low level of awareness of ICT, the transition to mixed learning, the availability of distance courses on distance learning platforms in Ukraine, the unsatisfactory quality of distance courses. The essence of distance learning is summarized, and the features of distance learning of students in the field of knowledge "Information Technologies" are given. The problems arising during distance learning in the knowledge "Information technologies" field have been identified. The quality of distance education and the role of ICT in providing it are described. A descriptive model of the quality of distance education using ICT in the field of knowledge "Information Technologies" is proposed. An expert study was conducted on the quality of education at the university on the example of the Lutsk National Technical University, the use of learning platforms, and types of ICT, a comparison was made with all-Ukrainian trends. The results of the survey and their analysis are presented. It is proposed to use mixed and distance (synchronous) forms of education. It has been established that the key component of quality distance education is the constant monitoring of processes and the development of NPPs, which are ready to convey explicit and implicit knowledge to students. This will be facilitated by a descriptive model of the quality of distance learning using ICT, which has three stages: description and characterization of the external environment, implementation of the model itself, and constant monitoring of goal achievement.